Finger Millet (Eleusine coracana) Plant–Endophyte Dynamics: Plant Growth, Nutrient Uptake, and Zinc Biofortification - Renu Chaudhary; Vijay Kumar; Sanjay Gupta; Bindu Naik; Ram Prasad; Sadhna Mishra; Per Erik Joakim Saris; Vivek Kumar (Microorganisms, 2023)
Endophytic fungi and bacteria were isolated from finger millet and their effects on finger millet growth parameters and zinc and NPK contents in grains were studied. Out of 70 fungal and 112 bacterial endophytes, the two best fungal and bacterial isolates were selected on the basis of zinc solubilization and plant-growth-promoting attributes. The fungal isolates identified were Aspergillus terreus and Lecanicillium sp., and the bacterial isolates were Pseudomonas bijieensis and Priestia megaterium. The endophytic zinc, NPK mobilization, and plant-growth-promoting efficacy were determined in a pot experiment with zinc carbonate as the zinc source. Endophytic-primed plants showed enhanced shoot and root lengths compared to the unprimed control. Endophytes increased the zinc content in grains by between 12.12% and 18.80% compared to control plants. Endophytes also augmented the NPK concentrations in seeds compared to control plants and exhibited stability in a diverse range of pHs, temperatures, and NaCl concentrations, and exhibited growth on various carbohydrate and nitrogen sources. This is the first study reporting the interaction of Aspergillus terreus, Lecanicillium sp., Pseudomonas bijieensis, and Priestia megaterium with finger millet for grain Zn biofortification and NPK concentration enhancement. This study indicated that zinc-dissolving endophytes possess the potential for enhancing the zinc and NPK content in grains in addition to the plant-growth-promoting attributes.